Kontroversi Khitan Perempuan: Tinjauan Fatwa Islam, Perspektif Medis, dan Regulasi Hukum di Indonesia - Wati, Risma; Nurlaila, Saila Nurul; Irpani, Nisrina Putri; Azhar, Muhammad Raihan Fadhil; Koswara, Sulthan Nadhif Anhaf Rabbani; Faozi, Akhmad; Supriyadi, Tedi (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
Female genital mutilation (FGM) is a debated practice in Indonesia, from religious, health and legal perspectives. This study aims to explore the views of religious leaders and medical professionals on the practice of female circumcision, and examine its compatibility with Islamic teachings, medical standards, and applicable regulations. This study used a qualitative approach with a semi-structured interview method involving five resource persons from among religious leaders and health professionals in the Sumedang area. Analysis was conducted using a thematic approach to identify patterns and views that emerged. The results showed that some religious leaders still view female circumcision as a sunnah action, but do not require its implementation, especially if it can cause harm. Meanwhile, from a medical perspective, this practice is considered to have no health benefits and can actually cause physical and psychological harm. The practice is also considered contrary to children's rights and is no longer legally recommended in Indonesia. This study concludes that there is a need for comprehensive education and collaboration between religious leaders, medical personnel, and policy makers to gradually prevent the practice of female circumcision through an approach based on religious values, health protection, and children's rights.